The UN global compact fair competition and environmental and labour justice in international markets - Gonzalez-Perez, Maria Alejandra; Leonard, Liam (Advances in sustainability and environmental justice ;, 2015)
Since UN Secretary-General Kofi Annan launched the Global Compact in 1999, over 12,000 organisations around the world have voluntarily adopted and promoted its values and Ten Principles in the areas of human rights, labour, environment and corruption. This corporate citizenship initiative has been seen as a non-compulsory alternative to international market regulations. Around the globe, the UN Global Compact has promoted the creation of local and regional networks for businesses to act together to mainstream the Ten Principles. This edited volume brings together international contributions on the specific implications for business when embracing the Global Compact. Managerial, internationalisation, legal, behavioural and sociological perspectives are explored in this volume in which both evidences and theoretical developments are reflected.